Nutritional status of 0-5 year old children of small scale fisherfolks from Barangays along the coastal areas of Miagao, Iloilo. - Ascano, Maria Epifanie; Borromeo, Ma. Benjafe (2003.)
The special problem sought to determine the nutritional status of 0-5 year old children of subsistence fisherfolks from selected barangays along the coastal areas of Miag-ao. The study incorporated anthropometric, clinical, dietary, and socio-economic data to detect any nutritional disorder and to ascertain nutriture of 0-5 years old children. There were fifty-six fishermen among the 14 coastal areas whih served as basis for determining the number of respondents. Ninety-one children aged 0-5 years old comprised the sample population. This descriptive cross-sectional study employed a probability sampling method named two-stage sampling design. This special study utilized an anthropometric data sheet, clinical assessment sheet, 24-hour food recall sheet, and interview schedule to gather appropriate data. The data collected was then subjected to statistical tools such as means, frequency count/distribution, percentages, ANOVA using the EPI-INFO 6 software and the Fil-Anthrop Software of the FNRI-DOST. Findings revealed that 45.1% of the respondents had an average height for age, 37.4% of the respondents were mildly underweight for age, and 54.9% had an average weight for height. Among the ninety-one respondents, the clinical signs exhibited were lack of luster, thinness, and spareness; dyspigmentation; pale conjunctiva; Thyroid gland enlargnebt; mottled enamel; dental caries; spongy; bleeding gums; and beading of rib. Moreover, 82.4% of the respondents were below the Recommended Dietary Allowance. Findings have revealed that there is no association between the nutritional status of respondents (ht for age, wt. for age, wt. for ht.) and the following variables: (a)Age of 0-5 years old children, (b)Sex of 0-5 years old children, (c)family size, (d)Monthly family income, (e)Highest educational attainment of housewives, (f)Clinical signs, (g)Sanitary practices, (h)Crowding index, (i)Feeding practices of housewives, (j)Presence of toilet facilities, and (k)Source of drinking water
Special Problem (Undergraduate, Bachelor of Science in Public Health)College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Children -- 0-5 year old -- nutritional status; Children -- Coastal Areas